Application of Electro-Fenton Oxidation of Refractory Organic Pollution - YAMINA MOUNIA, AZRI; DJILALI, ZEROUALI; AL-TAIAR, A.H. (Asian Journal of Chemistry, 2010)
In order to eliminate organic pollution contained in waste water of refinery, Electro-Fenton technique is applied to incinerate lubricate additive biocide N,N-methylenebismorpholine (C9H18N2O2). This process is based on a continuous electrogeneration of hydrogen peroxide in acidic solution by reducing the dissolved oxygen using an industrial graphite cathode. The cathodic potential, the electrolysis time and the dissolved oxygen level were systematically studied. The results obtained indicate that the optimal electrochemical conditions to electrogenerate hydrogen peroxide are: cathodic potential of -500 mV/SCE and current density of 1.4 mA/cm2. The production of hydrogen peroxide increased with the aeration and electrolysis time, then became stationary after approximately 2 h of electrolysis. Optimized parameters (potential, oxygen level and concentration of ferrous ions) were also applied to incinerate N,N-methylenebismorpholine. The incineration efficiency of the optimized parameters (potential, current density, COD/Fe2+ ratio and aeration) indicates that 97 % of COD was incinerated at 50 mA and the optimal concentration of catalyst is between 28 and 56 mg/L. The anode electro-activity of N,N-methylenebismorpholine offers other possibilities to oxidize directly this substance.